IMAGING PRINCIPLES IN DIAGNOSIS OF NASOPHARINGEAL LESIONS USING COMPUTED-TOMOGRAPHY AND MAGNETIC RESONANCE IN PAEDIATRIC PATIENTS - Diana-Andreea Ilinca; Roxana-Mihaela Balcan; Bogdan Ionut Dobrovat; Monica Boev; Emilia Adriana Marciuc; Letiția Doina Duceac; Oana Raluca Temneanu; Danisia Haba; Otilia Novac (Romanian Society of Oral Rehabilitation, 2023)
Aim of the study The aim of the study is to showcase the importance of the CT an MRI examination in the correct diagnosis of nasopharyngeal tumors in paediatric patients. Although nasopharyngeal cancer is rarely suspected in paediatric patients, representing only 1% of all malign tumors for this group age, its early detection is crucial for the prognosis of the patient. Material and methods We present a study lot of 83 patients assessed retrospectively that were diagnosed with nasopharyngeal lesions (benign adenoidian hypertrophy, juvenile angiofibroma, nasopharyngeal cancer and inverted papilloma) evaluated between April 2021- April 2022 in the Emergency Clinical Hospital "Prof. Dr. N. Oblu" Iasi, Romania. Although the majority of the diagnoses were incidentals during brain scan or MRI, we aim to showcase the principals of a CT and MRI neck examination in order to assess it correctly. Results and conclusions The CT and MRI imaging shown to be unmistakably an asset in diagnosis of nasopharyngeal lesions and also an ally in facilitating patient-based care.